Prophyll in Monocots: The Starting Point of Lateral Shoot Phyllotaxis - Choob, Vladimir (Frontiers in Plant Science, 2022)
In Monocots, the prophyll (or flower bracteole) is the first leaf of the lateral shoot. Typically, the prophyll occurs in an adaxial position towards the main axis, and bears two teeth at its apex and often two keels on the dorsal side. Some authors hypothesized, that prophyll appeared in evolution as a result of two phyllomes fusion. We tested this hypothesis and found, that in different monocot taxa, prophyll morphological characters depend on mechanical pressure of the surrounding organs and it could not be regarded to as two fused leaves. Our observations in Commelinaceae demonstrated, that if the lateral shoot develops extravaginaly and the prophyll is not under pressure, the apical teeth and keels are missing. If the lateral shoot starts development intravaginaly (under moderate pressure) prophyll exhibits keels and a bidentate shape. In bulbs of Amaryllidaceae (under strong squeeze) the teeth of the prophyll become more pronounced, and we find dissection of the prophyll into two distinct lobes. In some Monocots the evolutionary trend leads to the complete prophyll reduction. We discovered phyllotaxis of the lateral shoot and found, that the positions of all the subsequent phyllomes of the lateral shoot are sensitive to the prophyll position and becomes rearranged if the prophyll deviates from the standard adaxial location (e.g. becoming oblique or transversal). As a generalization of our observations in Amaryllidaceae we proposed the axiomatic “phantom” method for modelling of prophyll position and shoot branching in the cases of complete prophyll reduction. Using “phantom” method, we re-discovered the structure of sympodial units in Philodendron. The former interpretation of two-keeled cataphyll as a prophyll appeared to be erroneous. We proposed a new interpretation of the sympodial unit: the prophyll and the subsequent leaf are reduced, cataphyll is the third leaf in leaf series. Comparative morphological study in Araceae revealed, that prophylls of vegetative shoots practically do not elongate and look like round scales with obscure boundaries with the main axis. This observation could explain the prophyll reduction in Philodendron. As such, the positional control of phyllotaxis by the prophyll may be revealed even when the prophyll is completely reduced.